Penambahan Superplasticizer(0.4%) dan Additive Air Entrining AgentPada Campuran Beton Mutu fc 30 MPa. - Arrandi Risman, Ryan Ravi (Jurnal Vokasi Teknik Sipil, 2023)
Development in Indonesia has been very advanced, thus affecting the progress of building materials such as concrete. In practice, the development of concrete building materials requires a new innovation so that construction can be carried out properly and quickly. Concrete technological innovation is always required to answer the demand challenges, the resulting concrete is expected to have high quality including strength and durability without neglecting its economic value. The purpose of this study was to determine the compressive strength of cylindrical concrete with mixed design fc' 30Mpa with the addition of Air Entraining Agent. Based on the AEA brochure, added materials function to reduce the weight of concrete and reduce the use of cement in the mix. The concrete mix trials were divided into three treatments, namely with AEA doses of 0.03%, 0.06% and 0.14% respectively by weight of cement. The composition of the concrete mixture consists of 18.48 kg of cement, 42.7 kg of fine aggregate, 22.14 kg of coarse aggregate of 5-12 mm size, 41.10 kg of coarse aggregate of 10-20 mm size, 5.98 kg of water. The compressive strength test results for cylindrical concrete with 0.03% AEA added material were 30.95 MPa. The compressive strength of cylindrical concrete with 0.06% added AEA is 29.10 MPa. The compressive strength of cylindrical concrete with 0.14% added AEA is 26.55 MPa. The results of testing the weight of concrete without added ingredients were 12.385g. The weight of concrete with 0.14% added AEA is 10.065g. The weight of concrete with 0.06% added AEA is 11.710g. The weight of concrete with 0.03% added AEA is 12.170g. The more addition of Air Entraining Agent results in a decrease in the compressive strength and weight of the concrete.